2019
DOI: 10.1107/s2052252519010790
|View full text |Cite
|
Sign up to set email alerts
|

The DRS–AIMP2–EPRS subcomplex acts as a pivot in the multi-tRNA synthetase complex

Abstract: Aminoacyl-tRNA synthetases (ARSs) play essential roles in protein biosynthesis as well as in other cellular processes, often using evolutionarily acquired domains. For possible cooperativity and synergistic effects, nine ARSs assemble into the multi-tRNA synthetase complex (MSC) with three scaffold proteins: aminoacyl-tRNA synthetase complex-interacting multifunctional proteins 1, 2 and 3 (AIMP1, AIMP2 and AIMP3). X-ray crystallographic methods were implemented in order to determine the structure of a ternary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Previous X-ray crystallography data established a core of four GST-like domains that was not challenged by our results, and was used as a starting point in our model development ( 27 , 29 ). Our data showed AspRS cross-linked to two core constituents, namely, AIMP3 and MetRS – an unexpected result since previous biochemical and structural studies showed AspRS binding AIMP2 (Figure 1B ) ( 18 , 27 ). However, a recent report showed a 58-amino acid degradation fragment of AspRS (AspRS 336–393 ) resides in a crevice formed by AIMP2 and AIMP3 in the GST-like core ( 29 ).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Previous X-ray crystallography data established a core of four GST-like domains that was not challenged by our results, and was used as a starting point in our model development ( 27 , 29 ). Our data showed AspRS cross-linked to two core constituents, namely, AIMP3 and MetRS – an unexpected result since previous biochemical and structural studies showed AspRS binding AIMP2 (Figure 1B ) ( 18 , 27 ). However, a recent report showed a 58-amino acid degradation fragment of AspRS (AspRS 336–393 ) resides in a crevice formed by AIMP2 and AIMP3 in the GST-like core ( 29 ).…”
Section: Resultssupporting
confidence: 71%
“…MSC release of GluProRS and LysRS does not adversely influence cell viability, but their effects on MSC structure have not been investigated in depth. Although AspRS has been proposed to undergo stimulus-dependent release from the MSC ( 18 ), its central position suggests release might profoundly influence MSC structure. Consistent with previous electron microscopy showing a central location of AIMP1 ( 99 ), AIMP1 in our model forms a central belt-like structure interacting with multiple AARSs suggesting that release of intact AIMP1 might be detrimental to MSC structure.…”
Section: Discussionmentioning
confidence: 99%
“…While important progress has been made on the structure of the MSC, it is still not known in full molecular detail ( 51 , 65 , 66 ). We show here that arginyl-tRNA synthetase can be excluded from the MSC by ablation of its N-terminal leucine zipper (LZ) (Figures 2 and 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how the ArgRS LZ domain and GlnRS contribute to the nuclear distribution of the MSC, as neither contain nuclear localization sequences (NLS). Despite significant advances in our understanding of the MSC structure ( 51 , 65 , 66 ), it is yet unclear whether arrangements in the MSC could control exposure of other aaRS’s nuclear import or export cues upon ArgRS exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Other examples include binary or tertiary glutathione S-transferase (GST)-homology domain complexes: EPRS1 GST :AIMP2 GST , EPRS1 GST :EEF1E1, MARS1 GST :EEF1E1, and EPRS1 GST :AIMP2 GST :DARS1. 5,6 These assemblies are considered to be involved in flexible associations with each other to support subcellular translocations of EPRS1, MARS1, and EEF1E1 for their non-translational roles. [7][8][9] Other sub-interactions of the MSC are correlated with substrate tRNAs.…”
Section: Introductionmentioning
confidence: 99%